Preparative chromatography usage for release of monofractions of complex mixture from the natural sources - Фролова, Наталія Епінетівна; Українець, Анатолій Іванович; Силка, Ірина Миколаївна (Technology audit and production reserves, 2016)
An opportunity to use the laws and mechanisms of preparative gas chromatography to release of monofractions of complex mixtures is shown in the article. Scientific principles and practical development are given for manufacturing nozzle of preparative column, consisting of the stationary phase type Polyethylene glycol adipate-6000 deposited in batches on the solid support section of Chromosorb A. Nozzle is heterogeneous in nature and divided into sections with different dispersion of solid support and a different number of stationary phase on it. Selectivity factor of the column is 1,26±0,04 for this decision. The number of theoretical trays is 482±4.0. Productivity of carvone release is 8,67...9,05 cm3, cariofilen release – 3,46...3,51 cm3 per hour. Purity of released monofractions is 0,94...0,99. The proposed technological solutions preserve native connection, fully meet the requirements of natural products and can be used in any area of production.